CONVERSATIONAL ANALYSIS OF AI CHATBOT FEATURE OUTPUTS: CHATGPT IN FOCUS - Riezl May A. Clapiz; Jose Elmer S. Oficiar; Jella Mae V. Kudera; Anna Ronaliza G. Cervo (PUPIL: International Journal of Teaching, Education and Learning, 2026)
This research study was conducted to analyze and evaluate the ChatGPT’s chatbot feature outputs and is aimed to conceptualize how it could possibly be used as a tool to improve the English language proficiency of students if it is integrated in the educational system. We have analyzed the transcribed conversation between students and the AI chatbot, particularly ChatGPT, in terms of turn-taking and adjacency pairs. The research gathered corpus data from conversations with AI using the voice feature. It was analyzed using the theoretical lens of Adjacency Pairs Theory by Emanuel A. Schegloff and Harvey Sacks in 1973. After the corpus data was gathered, it was analyzed and categorized according to the following conversational adjacency patterns: (i) Greeting-greeting, (ii) Turn-taking Sequence, (iii) Repetition, (iv) Overlapping, and (v) Openings and Closings. Following the discourse analysis, this study employed a phenomenological approach to gain a robust understanding of the experiences of ChatGPT users and to affirm the data through triangulation and analyze its broader context. The results revealed the following themes: Accessibility and Convenience, Interactive Language Engagement, Academic Support, Confidence Builder, Vocabulary Development, Grammar Refinement, Language Fluency Development, Risks of Overreliance, Simplification of Complex Ideas, and Integration of Self-Paced Learning. The analysis identified patterns of natural conversation using turn-taking and adjacency pairs, thereby highlighting the benefits of conversations with AI Chatbots in improving students’ communication skills. The results of this study are viewed as significant for English learners to improve their communication skills and serves as an effective tool for the students to learn the language more efficiently with the absence of inhibitions or fear. This will not only improve the quality of education in the Philippines but also provide a conversational partner that is suitable for the communicative competence of L2 learners, integrating this tool into contextualized curricula, and pushing for a more effective way of addressing the needs and problems of the students in the context of English language competence.